Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Percetakan Prima Media Grafika Jember - Dita Hardini Prasanti (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This research examines the influence of work environment and work motivation on employee performance. The study was conducted at Percetakan Prima Media Grafika Jember using quantitative methods through multiple linear regression analysis. The sample in this study consisted of the entire population of 36 non managerial respondents. The data collection technique used in this study was a Likert scale questionnaire. The results of the study showed that the work environment had a positive and significant effect on employee performance partially. Work motivation showed a positive and significant effect on employee performance partially. The work environment and work motivation had a simultaneous effect on the employee performance variable. The work environment variable is the more dominant variable influencing employee performance compared to the work motivation variable. A conducive work environment and high work motivation will enhance employee performance at Prima Media Grafika Jember Printing Company
Reaploud Repository February_Hasyim
Keywords: Work Environment; Work Motivation; and Employee Performance